A randomized controlled trial comparing customized versus standard headrests for head and neck radiotherapy immobilization in terms of set-up errors, patient comfort and staff satisfaction (ICORG 08-09). Issue 1 (February 2015) - Howlin, C.; O'Shea, E.; Dunne, M.; Mullaney, L.; McGarry, M.; Clayton-Lea, A.; Finn, M.; Carter, P.; Garret, B.; Thirion, P.
Abstract Purpose To recommend a specific headrest, customized or standard, for head and neck radiotherapy patients in our institution based primarily on an evaluation of set-up accuracy, taking into account a comparison of patient comfort, staff and patient satisfaction, and resource implications. Methods and materials Between 2008 and 2009, 40 head and neck patients were randomized to either a standard (Arm A, n = 21) or customized (Arm B, n = 19) headrest, and immobilized with a customized thermoplastic mask. Set-up accuracy was assessed using electronic portal images (EPI). Random and systematic set-up errors for each arm were determined from 668 EPIs, which were analyzed by one Radiation Therapist. Patient comfort was assessed using a visual analogue scale (VAS) and staff satisfaction was measured using an in-house questionnaire. Resource implications were also evaluated. Results The difference in set-up errors between arms was not significant in any direction. However, in this study the standard headrest (SH) arm performed well, with set-up errors comparative to customized headrests (CHs) in previous studies. CHs require regular monitoring and 47% were re-vacuumed making them more resource intensive. Patient comfort and staff satisfaction were comparable in both arms. Conclusion The SH provided similar treatment accuracy and patient comfort compared with the CH. The large number of CHs that needed to be re-vacuumed undermines their reliability for radiotherapy schedules that extend beyond 34 days from the initial CT scan. Accordingly the CH was more resource intensive without improving the accuracy of positioning, thus the standard headrest is recommended for continued use at our institution.